Information and communication technologies in the context of globalization evidence from developing countries - Lal, Kaushalesh 1955- (Palgrave Macmillan, 2007)
This book focuses on the adoption of new technologies led by information and communication technologies by SMEs in developing countries. It identifies several factors that augment competitiveness of firms in the era of globalization. Contrary to the general belief these factors are not uniform across developing world. Based on the empirical evidence from firms located in Malaysia, India, Nigeria, Jamaica, and Costa Rica, the study concludes that firms cannot remain competitive without institutional support. Since firms operate in different institutional and economic environment, form of support varies from one country to another.